Positive feedback effects of Mg on the hydrolysis of poly-l-lactic acid (PLLA): Promoted degradation of PLLA scaffolds. (July 2018) - Shuai, Cijun; Li, Yang; Feng, Pei; Guo, Wang; Yang, Wenjing; Peng, Shuping
Abstract: The degradation rate of poly- l -lactic acid (PLLA) is too slow to match the growth rate of bone, which limits its application in bone transplantation. In this study, Mg was introduced into PLLA to increase the degradation rate. Three-dimensional porous PLLA/Mg scaffolds were fabricated via selective laser sintering. The results indicated that the introduction of Mg elevated the pH of the degradation medium and accelerated the weight loss of the scaffolds. These could be attributed to the alkaline product Mg(OH)2 from the degradation of Mg. It neutralized the acid degradation products of PLLA, which retarded the inhibition of the acid products on the degradation of PLLA. Meanwhile, the acid degradation products of PLLA could consume the alkaline product Mg(OH)2, promoting the degradation of Mg. The mutual neutralization between PLLA and Mg gave a positive feedback on the degradation of the scaffolds. Besides, the compressive strength, compressive modulus and Vickers hardness of the scaffolds were also increased due to the particle strengthening effect of Mg. In addition, the scaffolds showed good cytocompatibility. This study suggested the PLLA/Mg scaffolds may be a potential candidate of bone implants. Highlights: 3D interconnected porous PLLA/Mg scaffolds were fabricated via SLS. Mg had a positive feedback effect on promoting the degradation of PLLA. Mg enhanced mechanical properties of the PLLA/Mg scaffolds. Mg improved the cytocompatibility of PLLA scaffolds. PLLA/Mg scaffolds may be a potential candidate of bone implants.